Vibration characteristics and dynamic control of vacuum treatment - Velychko , O.G.; Sukhyy , K.M.; ZhouHua, Jiang (Theory and Practice of Metallurgy, 2023)
Vibration characteristics of vacuum treatment at industrial steel vacuumisation units are studied. The amplitude-frequency spectrum and the main sources of vibration of vacuum treatment units are analysed. It is shown that the vibration spectrum is dominated by low and high frequency ranges. In the low-frequency range the vibration of vacuum treatment units is connected with bath oscillations and wave formation on the surface, as well as with decarburisation of metal during oxygen blowing and vacuum-carbon deoxidation and degassing processes. In the high-frequency region the sources of vibration are pulsations of vented gases. Correlation relations between vibration and technological parameters of vacuum treatment are established. Possibilities of vibration method for dynamic control of vacuum treatment are shown. The character of vibration signal level change at the frequency of 8 Hz reflects the dynamics of decarburisation during oxygen blowing of metal at reduced pressure. In the established frequency ranges the vibration characteristics allow to control the processes of vacuum-carbon deoxidation and degassing.